Milling Dynamics and Propagation of Mechanically Activated Self-Sustaining Reactions - Alberto Cincotti; Gabriele Traversari; Giorgio Pia; Francesco Delogu (Advances in Materials Science and Engineering)
This work focuses on the propagation of mechanically activated self-sustaining reactions during the mechanical processing of powder in ball mills. We use a numerical model to reconstruct the dynamics of a single ball and powder particles inside the reactor of a SPEX Mixer/Mill 8000 under operational conditions. Taking advantage of the analytical description of the reactor swing, the equations of motion of ball and powder particles are solved numerically. The discrete element method is used to describe contacts. Reaction is ignited in an individual particle randomly selected among those compressed during an impact between ball and reactor. A simple kinetic law and a set of rules involving degree of chemical conversion and distance between particles are used to obtain a phenomenological description of the reaction propagation. We show that the propagation is significantly affected by reaction rate in individual particles, with other factors being less influential. We observe a strong coupling between the dynamics of powder particles and the reaction propagation.